Legal Protection for Directors Against Allegations of Directors' Negligence Resulting in Losses to the Company - Yoyo Arifardhani; Ibnu Masúd (Dinasti Research, 2026)
This study aims to analyze legal protection for directors against allegations of negligence resulting in losses for the company in the Indonesian legal system. The method used is normative legal research with a statutory approach and case studies through a comparative analysis of two court decisions, namely the Bekasi District Court Decision Number 647/Pdt.G/2021/PN Bks and the Surabaya District Court Decision Number 565/Pdt.G/2024/PN Surabaya. The results of the study indicate that the civil liability of directors is based on proof of the element of error or negligence, not solely on the occurrence of losses for the company. The Business Judgment Rule principle adopted through Article 97 paragraph (5) of Law Number 40 of 2007 concerning Limited Liability Companies provides conditional protection to directors who act in good faith, with professional prudence, and within the limits of legitimate formal authority. This study emphasizes the importance of a clear distinction between reasonable business risks and directors' negligence as a basis for determining legal liability proportionally and fairly.